Sonochemical Preparation and Subsequent Fixation of Oxygen-Free Graphene Sheets at N,N-Dimethyloctylamine-Aqua Boundary - Elena A. Trusova; Klara V. Kotsareva; Alexey N. Kirichenko; Sergey S. Abramchuk; Igor A. Perezhogin (Advances in Materials Science and Engineering)
In this study, the syntheses of oxygen-free graphene sheets and the method of its fixation at an oil-aqua interface were presented. The graphene sheets were prepared by exfoliation of synthetic graphite powder in an aqua-organic medium under ultrasound irradiation. N,N-Dimethyloctylamine- (DMOA-) aqua emulsion was used as the liquid medium, and pH was equal to 3. The obtained graphene nanosuspension was fractionated by sedimentation and decanted according to the weight. The graphene nanoparticle fractions, differing in configuration and number of layers, have been characterized using transmission electron microscopy (TEM), electron diffraction, HRTEM, Raman spectroscopy, and electron energy loss spectroscopy (EELS). It was found that using a DMOA-aqua mixture as the liquid medium in ultrasonic treatment of synthetic graphite leads to the formation of oxygen-free 1-2-layer graphene sheets attached to the DMOA-aqua interface. The proposed method differs from known ones by using a small amount of more environmentally friendly organic substances. It allows to obtain large quantities of oxygen-free graphene, and finally unconverted graphite can be directed for reuse. The proposed method allows to obtain both 2D graphene sheets with micron linear dimensions and 3D packages with a high content of defects. Both these species are in demand in areas related to the development of new materials with unique electrophysical properties.